Removal of Ni(II) from Aqueous Solution by Using Surfactant- EDTA Modified Amberlite XAD-7HP and Duolite XAD-761 Resins - THARANITHARAN, V.; SRINIVASAN, K. (Asian Journal of Chemistry, 2010)
The aim of this work is to evaluate the removal of Ni(II) from aqueous solutions by modified Amberlite XAD-7HP and Duolite XAD-761 resins. These modified resins have been individually prepared by complete mixing of parent resins with anionic surfactant-sodium dioctyl sulphosuccinate (SDOSS) and EDTA-disodium salt (chelating agent) in an aqueous solutions. The equilibrium adsorption level was determined as a function of contact time, pH and adsorbent doses. Adsorption isotherms of Ni(II) on adsorbents were determined and correlated with common isotherm equations such Langmuir and Freundlich models. The results showed that the adsorption kinetics of Ni(II) on modified XAD-7HP and XAD-761 resins could be best described by the pseudosecond- order model. The nickel(II) ions could be successfully recovered from the modified resin by treatment with 3-5 % NaCl. The modified resins thus regenerated could be used again to remove the heavy metal ions.